A nonstructural and antigenic glycoprotein is encoded by ORF3 of the IAF-Klop strain of porcine reproductive and respiratory syndrome virus - Gonin, P. (Arch Virol, 2014)
Open reading frame 3 (ORF3) of the genome of porcine reproductive and respiratory syndrome virus (PRRSV), Quebec strain IAF-Klop, was reverse-transcribed and cloned into the procaryotic expression vector pGEX-4T-1, then subcloned into the eucaryotic expression vector pAdCMV5 which was used as a shuttle vector to generate a replication-defective recombinant adenovirus. The procaryotic GST-ORF3 recombinant fusion protein was used to raise a monospecific antiserum in rabbits. By Western-immunoblotting with PRRSV-infected cell extracts, the ORF3 encoded protein had an estimated molecular mass (M(r)) of 42 kDa, similar to that of the protein expressed by the adenovirus vector. Endoglycosidase F digestion showed that the ORF3 encoded protein occurs in an highly glycosylated form (GP(3)) in the infected MARC-145 cells. Pulse-chase and radioimmunoprecipitation experiments revealed that the GP(3) protein was present in amounts equivalent to those of the N, M, and GP(5) proteins in the infected cells, whereas no GP(3) could be detected in purified virions. During the first 30 min of chase, the GP(3) undergoes a gradual downward shift of its apparent M(r), thought to result from trimming of the mannose-rich glycan structures. Tested convalescent pig sera that were found to be seropositive to PRRSV by indirect immunofluorescence reacted positively with the recombinant GST-ORF3 fusion protein by immunoblotting. Data indicated that the ORF3 protein of the Quebec reference strain of PRRSV is a highly glycosylated and antigenic protein, which is nonstructural.